Structural and biophysical properties of a synthetic channel-forming peptide: designing a clinically relevant anion selective pore - Bukovnik, U.; Gao, J.; Cook, G. A.; Shank, L. P.; Seabra, M. B.; Schultz, Bruce D.; Iwamoto, T.; Chen, J.; Tomich, John M. (My University, 2012)
The design, synthesis, modeling and in vitro testing of channel-forming peptides derived from the cys-loop superfamily of ligand-gated ion channels are part of an ongoing research focus. Over 300 different sequences have been prepared based on the M2 transmembrane segment of the spinal cord glycine receptor α-subunit. A number of these sequences are water-soluble monomers that readily insert into biological membranes where they undergo supramolecular assembly, yielding channels with a range of selectivities and conductances. Selection of a sequence for further modifications to yield an optimal lead compound came down to a few key biophysical properties: low solution concentrations that yield channel activity, greater ensemble conductance, and enhanced ion selectivity. The sequence NK[subscript]4-M2GlyR T19R, S22W (KKKKPARVGLGITTVLTMRTQW) addressed these criteria. The structure of this peptide has been analyzed by solution NMR as a monomer in detergent micelles, simulated as five-helix bundles in a membrane environment, modified by cysteine-scanning and studied for insertion efficiency in liposomes of selected lipid compositions. Taken together, these results define the structural and key biophysical properties of this sequence in a membrane. This model provides an initial scaffold from which rational substitutions can be proposed and tested to modulate anion selectivity. This article is part of a Special Issue entitled: Protein Folding in Membranes.
Keywords: Channel-forming peptide; Self-assembly; Glycine receptor; Pore structure